Crystal Structures and Spin‐Crossover Behavior of Iron(II) Complexes with Chiral and Racemic Ligands. Issue 7 (15th February 2017) - Sekimoto, Yusuke; Karim, Mohammad Razaul; Saigo, Naoto; Ohtani, Ryo; Nakamura, Masaaki; Hayami, Shinya
Abstract: Invited for the cover of this issue is the group of Shinya Hayami at Kumamoto University, Japan. The cover image shows a Japanese New Year's card symbolizing the dawn of a new era for chiral magnetism. Mt. Aso, which is the symbol of Kumamoto, was chosen for the background. Abstract : We believe that our strategy is useful in the design of next‐generation magneto‐optical compounds… Read more about the story behind the cover in the Cover Profile and about the research itself on page 1049 ff (DOI:10.1002/ejic.201601232 ).